Longman language activator : helps you write and speak natural English (Harlow, Essex, England : Pearson, 2002)
This new edition makes it easier for the for you to write and speak English. It contains thousands of new written and spoken corpus examples showing usage.
Includes index.
ne 28/09/2021
Ref.
Keywords: English language--Usage; Synonyms